(untitled) (mathematica didactica, 2022)
Geometric objects and their relations must be represented in order to be communicated, acquired and understood. We discuss the significance of various forms of representations of geometric objects. We show that the dynamic geometry software GeoGebra not only allows the construction and illustration of geometric relations but also the historical reconstruction of sources, which only document the final result of the construction. We illustrate our considerations with some geometric constructions in Albert Einstein’s manuscripts.